CLN8 disease caused by large genomic deletions. Issue 1 (23rd November 2016) - Beesley, Clare; Guerreiro, Rita J.; Bras, Jose T.; Williams, Ruth E.; Taratuto, Ana Lia; Eltze, Christin; Mole, Sara E.
Abstract: Background: The presence of deletions can complicate genetic diagnosis of autosomal recessive disease. Method: The DNA of patients was analyzed in a diagnostic setting. Results: We present three unrelated patients each carrying deletions that encompass the 37 kb CLN8 gene and discuss their phenotype. Two of the cases were hemizygous for a mutant allele – their deletions unmasked a mutation in CLN8 on the other chromosome. Conclusion: Microarray analysis is recommended in any patient suspected of NCL who is apparently homozygous for a mutation that is not present in one of the parents or when the family has no known consanguinity. Abstract : We present three unrelated patients each carrying deletions that encompass the 37 kb CLN8 gene. Two of the cases were hemizygous for a mutant allele.